2016
DOI: 10.2175/106143016x14609975747045
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Intrusion Impacts on the Water Quality of the Groundwater on theNorthwest Coast of Oman

Abstract: The groundwater aquifer in the coastal region of the northwest of Oman has been used extensively since the early 1980s for agricultural, industrial and municipal purposes. The over pumping of this reservoir has led to the intrusion of seawater and therefore to the deterioration of the groundwater quality. In this study, an investigation was carried out in the southern part of this region to identify the quality of groundwater, to understand the main sources of groundwater mineralisation, and to check the suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…He reported that under the prevailing conditions, the groundwater levels in Salalah area would drop significantly allowing for the inland advancement of seawater. Ahmed and Askeri [ 73 ] studied the seawater intrusion impact on the groundwater quality of the northwest coast of Oman. The seawater intrusion was reported to extend inland up to 8 km from Oman's coast.…”
Section: Water Resources In Gcc Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…He reported that under the prevailing conditions, the groundwater levels in Salalah area would drop significantly allowing for the inland advancement of seawater. Ahmed and Askeri [ 73 ] studied the seawater intrusion impact on the groundwater quality of the northwest coast of Oman. The seawater intrusion was reported to extend inland up to 8 km from Oman's coast.…”
Section: Water Resources In Gcc Countriesmentioning
confidence: 99%
“…Managed aquifer recharge (MAR) technology and its derivatives Soil Aquifer Treatment (SAT) and Aquifer Storage and Recovery (ASR) represent a new technique for supply side management [ 63 , 73 , 82 ]. A number of GCC countries started to investigate the use of MAR/SAT/ASR to improve water supply management and sustainability, including small- and large-scale flood capture and banking (MAR and ASR), tertiary wastewater treatment through SAT, and banking of desalination water in brackish aquifers (ASR).…”
Section: Future Assessment and Management For The Year 2050mentioning
confidence: 99%
“…The degree of SWI is expected to associate with the climate change effects like an increase in sea-level and rise of temperature and reduction of precipitation, coupled with excess groundwater abstraction. The origin of SWI is wide-ranging, for example, over-withdrawal and the variation between the densities of seawater and freshwater [26]. The manifestation of SWI owing to over-exploitation of groundwater detectable within the coastal regions because of a decline in groundwater levels [27].…”
Section: Seawater Intrusion (Swi)mentioning
confidence: 99%
“…Cases of salt water incursion into coastal aquifer and its consequential effect on the quality of portable fresh water as well as lives and properties, have received worldwide attention and has been reported in several parts of the world (Qi and Qiu 2011 [1]; Werner et al, 2012 [2]; Edwards and Evans 2013 [3]; Elsheikh and Zeinelabdein 2015 [4]; Ahmed and Askri 2016 [5]; Gururaja et al, '2019[6]; Behera et. al.'…”
Section: Introductionmentioning
confidence: 99%